30 Rock - Season 1 Episode 1-21 - Bernstein, Adam; Mancuso, Gail; Scardino, Don; Houghton, Tom; Trim, Michael; Fey, Tina; Baldwin, Alec; Morgan, Tracy (Universal Pictures, 2016)
Art imitates life in this smart comedy starring Saturday Night Live alums Tina Fey, Tracy Morgan, and frequent host Alec Baldwin. In addition to writing and executive producing "30 Rock", Fey plays Liz Lemon, the head writer on a variety series called "The Girlie Show". But the new Vice President of East Coast Television, Jack Donaghy (Baldwin), decides to shake up the show, adding eccentric actor Tracy Jordan (Morgan) to the cast and changing the name. A critical hit, "30 Rock" garnered a Golden Globe win for Fey in its first series for its brand of comedy that ably straddles intelligence and silliness. This sitcom also features Jane Krakowski (Ally McBeal), Scott Adsit (Kicking and Screaming), and Judah Friedlander. But with such a deep bench of talent, the show's secret weapon is Kenneth, played by Jack McBrayer (Arrested Development), whose naivete is a hilarious contrast to the rest of the characters. [www.amazon.co.uk]
Keywords: DVD-Video